Motivasi Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Di Smp Negeri 1 Benteng Kabupaten Indragiri Hilir - hamzah, hamzah (Jurnal Edukasi, 2024)
This research aims to find out the motivation of students in the learning of sports education, sports and health in the State Primary School I Fortress Indragiri Hilir district.This type of research is descriptive and where the site of the research is in the State High School I Fortress, as well as where the population in this study is a total of 17 students as respondents with sampling using the total sampler technique, which obtained samples of a total 17 students. The instruments used in this research are an angket or questionnaire or question using a guttmen scale where data is analyzed using a frequency distribution formula in the form of percentages.From the data analysis results obtained as follows: 1) The level of accessibility for subvariable motivation instrinsic students in learning penjasorkes in SME State I Fortress Indragiri district Hilir of 87,06% with accessibility classification category good. 2).